2008
DOI: 10.1523/jneurosci.3098-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Group I Metabotropic Glutamate Receptors Control Metaplasticity of Spinal Cord Learning through a Protein Kinase C-Dependent Mechanism

Abstract: Neurons within the spinal cord can support several forms of plasticity, including response-outcome (instrumental) learning. After a complete spinal transection, experimental subjects are capable of learning to hold the hindlimb in a flexed position (response) if shock (outcome) is delivered to the tibialis anterior muscle when the limb is extended. This response-contingent shock produces a robust learning that is mediated by ionotropic glutamate receptors (iGluRs). Exposure to nociceptive stimuli that are inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 92 publications
(147 reference statements)
4
58
0
Order By: Relevance
“…Following surgery, the wound was closed with Michel clips. T12 level contusion models have been routinely used by members of our group to define spinal cord learning circuits and molecular mechanisms involved with recovery of function (Brown et al, 2011; Ferguson et al, 2008; Hook et al, 2011). Lesions at this level result in well-defined and replicable sensory-motor deficits, and we therefore chose to utilize contusion at this level to also examine changes in miRNA expression.…”
Section: Methodsmentioning
confidence: 99%
“…Following surgery, the wound was closed with Michel clips. T12 level contusion models have been routinely used by members of our group to define spinal cord learning circuits and molecular mechanisms involved with recovery of function (Brown et al, 2011; Ferguson et al, 2008; Hook et al, 2011). Lesions at this level result in well-defined and replicable sensory-motor deficits, and we therefore chose to utilize contusion at this level to also examine changes in miRNA expression.…”
Section: Methodsmentioning
confidence: 99%
“…For subjects in the fixed spaced condition, shocks occurred at regular (2-s) intervals. Variable stimulation was created using a rectangular distribution that varied between 0.2 and 3.8 s, with a mean interstimulus interval (ISI) of 2 s. Prior work has shown that variable shock undermines learning (Crown et al, 2002; Baumbauer et al, 2007; Baumbauer et al, 2008; Ferguson et al, 2008; Baumbauer et al, 2009), while fixed shock does not (Baumbauer et al, 2008; Baumbauer et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…[124][125][126][127] Several groups have subsequently demonstrated the existence of metaplasticity in spinal cord locomotor circuitry below SCI. [128][129][130][131][132] Understanding spinal cord (re)-training potential as a form of metaplasticity provides a fertile literature to draw from for pharmacological targets to carefully tune and improve spinal cord training after injury.…”
Section: Nociceptive/noxious Afferent Inputmentioning
confidence: 99%